2012
DOI: 10.1080/09540121.2012.674097
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk perceptions among adolescents attending family planning clinics: An integrated perspective

Abstract: The current study assessed the impact of individual, interpersonal, and contextual factors on HIV risk perception. A total of 426 female adolescents attending family planning clinics took part in this study. The majority, 60.1% were African-American and 39.9% were Hispanic. The results indicated that the majority of participants perceived themselves to be at no or low risk for contracting HIV. Individual, interpersonal as well as contextual factors correlated with HIV risk perception in the study. Adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Nevertheless, more than half of our participants were not motivated to be tested, confirming the impression that many adolescents do not consider themselves at risk even though their behavior is risky. [11][12][13][14]53 A study on acceptance of an HIV test offer showed that even after administration of a self-risk checklist assessment tool, only * 50% of adolescents at risk accepted an offer of an HIV test, with African American adolescents accepting more often than Latino adolescents. 54 HIV/AIDS knowledge and awareness of an adolescent's own risk behavior may be necessary, but not sufficient, to change health risk or protective behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more than half of our participants were not motivated to be tested, confirming the impression that many adolescents do not consider themselves at risk even though their behavior is risky. [11][12][13][14]53 A study on acceptance of an HIV test offer showed that even after administration of a self-risk checklist assessment tool, only * 50% of adolescents at risk accepted an offer of an HIV test, with African American adolescents accepting more often than Latino adolescents. 54 HIV/AIDS knowledge and awareness of an adolescent's own risk behavior may be necessary, but not sufficient, to change health risk or protective behavior.…”
Section: Discussionmentioning
confidence: 99%
“…They may not think that they are at risk for HIV but are not ruling out the possibility that they are at risk for HIV simply because they are young. Since they are more aware of the potential risk, safer sexual behaviors are selected (e.g., monogamy; a low-risk profile as in Buzi, Smith, Weinman, & Novello, [2013]). Also, perceived HIV risk is known among the sample, but the likelihood of HIV infection, a potential moderator of the relationship, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Perceiving HIV vulnerability has influenced condom use among African American and Latino adolescent and young adult males (Brooks, Lee, Stover, & Barkley, 2011;Kennedy et al, 2007). Buzi, Smith, Weinman, and Novello (2013) found that females utilizing family planning clinics and with low HIV risk perception are more likely to be Latina and exhibit lower risk behaviors (e.g., fewer sexual partners), but their use of condoms is unknown. When the relationship between perceived susceptibility and condom use is explored among females, perceived susceptibility is tailored to pregnancy or sexually transmitted infections [STI].…”
Section: Intrapersonal Correlates Of Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…An integrated approach that simultaneously accounts for multiple dimensions of adolescents’ characteristics appears to be necessary to understanding their perceived risk of HIV . According to a study of young black and Hispanic female family planning clinic clients that—unlike previous studies—included individual, interpersonal and contextual variables, 47% of youth perceived that they had no risk of HIV, 37% thought they had a low risk and 16% thought they had a medium or high risk.…”
mentioning
confidence: 99%